Literacy difficulties : diagnosis and instruction - Block, Cathy Collins (Fort Worth, TX : Harcourt Brace College, 1997)
Foundations. Conditions that can impede literacy development. Instructional adaptations in reading. Instructional adaptations in language arts. Specialized adaptations.
Keywords: Education; Reading -- Ability testing; Reading -- Remedial teaching; Reading disability